PENGARUH SELF EFFICACY, INSENTIF, DAN QUALITY OF WORK LIFE TERHADAP PENGEMBANGAN KARIR KARYAWAN DI KANTOR PT. CIPTA GAGAS LESTARI KOTA PONOROGO - Rizki Dwi Puspita Rini; Umi Farida; Eka Destriyanto Pristi A. (Jurnal AKTUAL, 2023)
The background of this research is that employees complain about demands from companies where the work is not in accordance with their jobdesk, the incentives they get are not in accordance with what they are doing. In this study the researcher aims to examine whether there is an effect of self-efficacy, incentives, and quality of work life on employee career development at the Pt.Cipta Gagas Lestari Office, Ponorogo City. The method in this study uses a descriptive approach with multiple linear regression analysis where this technique aims to show whether there is an influence between the independent variables on the dependent variable. If the coefficient of determination is R²0, it means that the independent variable has no effect at all (0%) on the dependent variable. Conversely, if the coefficient of determination is R²1, it means that the dependent variable is 100% influenced by the independent variable. The results of this study indicate that self-efficacy, incentives, and quality of work life simultaneously affect the career development of employees at the PT.Cipta Gagas Lestari Ponorogo Office. This is evidenced by the results of the F test where F count 12.226 F table 2.79 with a significance of 0.000 0.05. Self-efficacy, incentives, and quality of work life simultaneously influence the career development of employees at the PT. Cipta Gagas Lestari Ponorogo Office.